Genome Analysis of Rift Valley Fever Virus, Mayotte - Cêtre-Sossah, Catherine (Centers for Disease Control and Prevention, 2012)
As further confirmation of a first human case of Rift Valley fever in 2007 in Comoros, we isolated Rift Valley fever virus in suspected human cases. These viruses are genetically closely linked to the 2006–2007 isolates from Kenya.